2019
DOI: 10.1080/00288233.2019.1616568
|View full text |Cite
|
Sign up to set email alerts
|

Triplet lambs and their dams – a review of current knowledge and management systems

Abstract: Triplet-bearing ewes and their lambs have the potential to improve flock productivity however, the lack of robust information on optimal nutrition and management is limiting their performance. In comparison to twins, the triplet lamb is; lighter, more metabolically challenged, has lower body temperature, and receives less colostrum and milk which combined results in lower survival rates and weaning weights. While scientifically based management guidelines are available for singletons and twins, guidelines are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 183 publications
(343 reference statements)
5
29
1
1
Order By: Relevance
“…Mortality rates in this study were within the range of those previously reported for both twin-(8.1% to 26.7%) and tripletborn (12.7% to 53.4%) lambs managed under extensive pastoral systems in New Zealand [2,17]. The relationship between the sex of the lamb [18] and a curvilinear relationship of lamb birth weight [19,20] with survival to weaning were also consistent with previous work.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Mortality rates in this study were within the range of those previously reported for both twin-(8.1% to 26.7%) and tripletborn (12.7% to 53.4%) lambs managed under extensive pastoral systems in New Zealand [2,17]. The relationship between the sex of the lamb [18] and a curvilinear relationship of lamb birth weight [19,20] with survival to weaning were also consistent with previous work.…”
Section: Discussionsupporting
confidence: 91%
“…Lamb mortality is of concern to the New Zealand sheep industry from both an economic and an animal welfare perspective [ 1 ]. New Zealand studies conducted in outdoor pastoral conditions have reported lamb losses from birth to weaning of 14% to 20% for twin-born lambs and 28% to 56% for triplets [ 2 ]. An understanding of the factors involved in multiple-born lamb mortality could improve ewe flock productivity through the development of strategies to reduce lamb mortality.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that supplementing different sources of fatty acids reduces the latency to suckle (Rocha et al, 2018) in pregnant ewes. Also, Kenyon et al (2019) noticed that triplet-bearing ewe displayed a longer period of restlessness prior to lambing than both singleton and twinbearing ewes.…”
Section: Effect Of Ration On Lambs Behavior :-mentioning
confidence: 94%
“…In addition, Hamdon (2009) shows that average suckling milk such as , fat, protein and energy pre-weaning were 28.08 L, 4.93%, 434% and 3.54 MJ/L in Sohagi sheep, respectively. Moreover, Kenyon et al (2019) found that increasing litter size was associated with a decline in the duration of suckling. Recently, Shereef (2020) found that either 17% of protein or 331 of calories were supplied to ewes' ration could be improved total protein, linoleic acid, omega 3 and unsaturated fatty acids in ewes' milk.…”
Section: Fat Protein and Energy Amount In Suckling Milk :-mentioning
confidence: 99%
“…The importance of creep grazing for lamb production worldwide has been recognized for more than 60 years ( 52 ). Creep grazing has been mentioned not only as an additional feed ( 53 ) but also as a management tool for controlling parasitic infection in lambs ( 54 ). However, very few studies have been carried out in subtropical regions with grazing ewes using tropical grass species.…”
Section: Grazing Sheep Management and Supplementationmentioning
confidence: 99%